EFEKTIVITAS KOMBINASI METODE INFORMASI GIZI DAN PELATIHAN DUKUNGAN SOSIAL DALAM PENINGKATAN INTERAKSI 1BU-ANAK DAN STATUS GIZI ANAK - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT Based on previous studies and the initial survey in Gedong Tengen, Yogyakarta, the researcher found that there was still a problem of malnutrition on children aged 4-6 years old. The survey also showed that mothers had difficulties in enhancing "nutrition awareness" on children. Moreover in the process enhancing "nutrition awareness" on children could even cause a negative interaction between mother and children. This research is an experiment to compare the effectivity between pro- viding information method with social support skill training and without social support skill training in enhancing mother-child interaction and children's nutrition status. The prepost controlled group design was applied on the subjects. Data was collected by the Nutrition Knowledge Test, the Eating Habit Questionnaire, the Average of Calory Intake by children everyday and observed mother-child interacfion. The subjects were mothers and their children aged 4-6 years old who had malnutrition problems. Experiment went on for seven weeks. There were weekly meetings for 90 to 120 minutes each. Data on initial and final measuremens on the experimental and control groups were analized statistically with One-way Analysis of Variance (Mixed Model). The quantitative analysis shows that a combination between nutrition information method and social support skill training is eveffective in enhancing mother's nutrition knowledge (p = 0.000), children's healthy eating habit (p = 0.0135), childrens nutrition status (p = 0.000), and positive mother-child interaction (p = 0.0025).